Spatial Mapping of Dengue Fever Cases Using Quantum GIS in Kendari City Indonesia - Andi Mauliyana; Anry Hariadhin Depu (Waluya The International Science of Health Journal, 2026)
Introduction: The increasing number of Dengue Hemorrhagic Fever (DHF) cases in Kendari City indicates the need for more effective spatial data-based control efforts. This study aims to conduct Spatial Mapping of Dengue Fever Cases Using Quantum GIS in Kendari City, Indonesia. Method: This type of research is descriptive quantitative with an observational approach. The study population includes all 15 Community Health Centers under the auspices of the Kendari City Health Office, with DHF case data for the 2022–2024 period obtained from the Kendari City Health Office. Data were analyzed using spatial methods with Quantum GIS software to display case distribution trends, case detection rates, and treatment outcomes. Result: The results show that the trend of cases in Kendari City experienced a significant increase from 2022 to 2024, with the highest spike in 2024 of 1,689 cases. The community health centers with the highest number of cases were in Lepo-Lepo, Poasia, and Mokoau, while the lowest number of cases were in Mata and Nambo. Conclusion: The distribution map shows that areas with high population density and poor sanitation conditions are at greater risk of dengue transmission. It is recommended that the Kendari City Health Office utilize the results of this mapping as a basis for determining priority intervention areas and improving the GIS-based surveillance system for sustainable dengue control.